(untitled) (Eurasian Journal of History, Geography and Economics, 2026)
This study examines the economic efficiency of tourism and its impact on the labor market in Uzbekistan, with a focus on tourism-related income, consumption patterns, and employment in legal entities. Using statistical data from the State Committee of the Republic of Uzbekistan on Statistics, the Ministry of Employment and Labor Relations, and international tourism databases (UNWTO, 2022), the research applies descriptive, comparative, and regression analyses to evaluate tourism’s contribution to the national economy and labor market dynamics. The findings indicate that tourism significantly stimulates household income, increases consumption in the service sector, and generates both direct and indirect employment opportunities. Regional disparities in tourism development and workforce allocation are identified, highlighting the importance of policy measures to enhance infrastructure, support workforce training, and promote sustainable tourism practices. The study provides empirical evidence for policymakers and stakeholders to integrate tourism strategically into national economic planning, aiming to maximize its socio-economic benefits and labor market contributions.